"Conchostracan" Records from Western Gondwana Related to Cretaceous Palaeoclimatic Features - Gallego, Oscar Florencio (2019)
Cretaceous System is widely represented in South America. “Conchostracans” are best represented with 47 early Cretaceous species and only 5 Late Cretaceous ones. Its warm climate with rainfall and marked seasonality allowed the development of the “conchostracan” populations. This information shows that more detailed analysis between climate and “conchostracan” records is needed to reconstruct environments in the Cretaceous times.